The PRRSV-Specific Memory B Cell Response Is Long-Lived in Blood and Is Boosted During Live Virus Re-exposure - Rahe, Michael C.; Dvorak, Cheryl M. T.; Patterson, Abby; Roof, Michael; Murtaugh, Michael P. (Frontiers in Immunology, 2020)
Porcine reproductive and respiratory syndrome virus (PRRSV) is an important pathogen of swine health and wellbeing worldwide largely due to an insufficient understanding of the adaptive immune response to infection leading to ineffective PRRSV control. The memory and anamnestic response to infection are critical gaps in knowledge in PRRSV immunity. The lack of effective tools for the evaluation of the memory response previously hindered the ability to effectively characterize the porcine memory response to infection. However, the creation and validation of a PRRSV nsp7-specific B cell tetramer now facilitates the ability to detect very rare memory B cells and thus define the memory response of the pig. Here, we describe the PRRSV nsp7-specific B cell response following vaccination and challenge in six key secondary lymphoid organs including the identification of PBMCs as the tissue of interest for the memory immune response in pigs. Following live virus challenge of immune animals, an anamnestic response of nsp7-specific memory B cells and neutralizing antibodies was observed. This characterization of the functional humoral immune response to PRRSV answers key questions involved in regional specialization of the immune response following intramuscular inoculation of PRRSV MLV.